Isthmic tubal ectopic pregnancy from a partial molar pregnancy: A case report and literature review - Richard Q. Vuong; Molly Hurd; Zeynep Tek; Nicole Brzozowski (Case Reports in Women's Health, 2025)
While tubal ectopic pregnancies and molar pregnancies are relatively common, tubal molar pregnancies are exceptionally rare, with an estimated incidence of 1.5 per 1,000,000 pregnancies. Molar pregnancies are at risk for developing malignant gestational trophoblastic neoplasia (15–20 % for complete hydatidiform moles and 0.5–6 % for partial hydatidiform moles) and warrant robust diagnostic workup to determine appropriate management. Presented here is a case of an isthmic tubal ectopic pregnancy secondary to a partial hydatidiform mole; additionally, a literature review through PubMed discusses all tubal molar pregnancies reported within a 5-year period.A 41-year-old woman (gravida 2, para 0, aborta 1) at 6 weeks and 5 days of gestation presented to the emergency department from the outpatient clinic because prenatal ultrasound did not show an intrauterine pregnancy and her a β-hCG level was 17,913 mIU/mL. Due to concern for ectopic pregnancy, she underwent diagnostic laparoscopy, which revealed an unruptured right isthmic tubal ectopic gestation. The specimen was removed and sent for histological evaluation, which confirmed a partial hydatidiform mole that stained positive for p57; the finding was supported by molecular studies. The patient was discharged the same day and follow-up β-hCG levels were monitored weekly until undetectable. The literature review found that 13 tubal molar pregnancies had been reported between 2019 and 2024.Histopathologic examination of gestational trophoblastic disease should be supported by ancillary studies such as immunohistochemical, flow cytometry, and molecular analyses to ensure accurate diagnosis. Magnetic resonance imaging could offer a way to preoperatively diagnose molar ectopic pregnancy in select hemodynamically stable patients.